Effects of soil mechanical properties on the height and tractive performance of rubber grouser at different moisture contents - Shaikh, Sher Ali; Li, Yaoming; Ma, Zheng; Chandio, Farman Ali; Tunio, Mazhar Hussain; Ahmad, Fiaz; Solangi, Kashif Ali (International Journal of Agricultural and Biological Engineering, 2022)
Rubber tracked vehicles are commonly used on agricultural machinery that perform agricultural operations such as rice harvesting in soft paddy fields with low bearing capacity. Research was carried out to assess the influence of soil moisture content and mechanical properties on the tractive performance of a rubber grouser with three heights (45 mm, 55 mm, 60 mm). The direct shear test and penetration test were used in this study, which was based on a semi-empirical approach of determining tractive parameters. Direct shear tests were used to measure soil shear strength parameters such as cohesion, adhesion, internal and exterior friction angles. The results of the penetration test were used to determine tractive parameters such as soil thrust, running resistance, and traction, for the penetration test, a device was designed and developed. The experimental results revealed that soil cohesion and adhesion increased linearly with increasing soil moisture content, however adhesion dropped after 30.7%. Similarly, the soil thrust initially increased till 21.5% then decreased. Furthermore, running resistance had a decreasing trend over soil moisture content whereas maximum traction achieved for 45 mm grouser height at 21.5% moisture content. It was concluded that a rubber grouser with 45 mm height had better traction rather than 55 mm and 60 mm, it can be suitably used for designing a track system for a crawler vehicle (e.g., harvester) leading to its greater adoption among the farmers. Keywords: soil moisture content, traction, rubber grouser, soil mechanical properties, tracked vehicle DOI: 10.25165/j.ijabe.20221506.7137 Citation: Shaikh S A, Li Y M, Ma Z, Chandio F A, Tunio M H, Ahmad F, et al. Effects of soil mechanical properties on the height and tractive performance of rubber grouser at different moisture contents. Int J Agric & Biol Eng, 2022; 15(6): 31–37.